2001
DOI: 10.1046/j.1460-2695.2001.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Weibull stress model for cleavage fracture under high‐rate loading

Abstract: This paper examines the effects of loading rate on the Weibull stress model for prediction of cleavage fracture in a low‐strength, A515‐70 pressure vessel steel. Interest focuses on low‐to‐moderate loading rates (K˙I < 2500 MPa √m s−1 ). Shallow cracked SE(B) specimens were tested at four different loading rates for comparison with previous quasi‐static tests on shallow notch SE(B)s and standard C(T)s. To utilize these dynamic experimental data, we assume that the Weibull modulus (m) previously calibrated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Petti and Dodds have subsequently coupled the microscopic crack driving force, σ w , with the macroscopic crack driving force, K JI , with a constraint function to characterize the plasticity‐induced constraint loss in fracture specimens. Many research efforts have confirmed the close agreement between the experimentally measured macroscopic fracture toughness with the three‐parameter Weibull stress model. The calibration of the three‐parameter Weibull stress model often requires significant experimental efforts with carefully controlled and instrumented results.…”
Section: Introductionmentioning
confidence: 59%
“…Petti and Dodds have subsequently coupled the microscopic crack driving force, σ w , with the macroscopic crack driving force, K JI , with a constraint function to characterize the plasticity‐induced constraint loss in fracture specimens. Many research efforts have confirmed the close agreement between the experimentally measured macroscopic fracture toughness with the three‐parameter Weibull stress model. The calibration of the three‐parameter Weibull stress model often requires significant experimental efforts with carefully controlled and instrumented results.…”
Section: Introductionmentioning
confidence: 59%
“…Ruggeiri et al [14] studied the impact of constraint loss on T 0 using the Weibull stress model. In the year 2001, Gao et al [15] investigated the influence of loading rate on the Weibull parameters at low to moderate loading range and they found that m is invariant in low loading range, but σ u is strongly rate sensitive. Gao et al [16] also proposed that σ u must be calibrated in dynamic loading range.…”
Section: Introductionmentioning
confidence: 99%
“…Sin ISSN: 2594-1925 embargo, Kim (2011) y Huang (2017) determinan los esfuerzos normales basado en pruebas experimentales en elementos estructurales, con el objetivo de determinar parámetros de experimentales de fatiga de los estos elementos. Actualmente, algunas metodologías probabilísticas de análisis de esfuerzo-resistencia parten del hecho de la existencia de este esfuerzo normal sin especificar el modo de determinación del mismo [1][2][3], [17][18][19].…”
Section: Introductionunclassified